Optimizing Nano Metalworking Emulsions Preparation Using Response Surface Method - Nuhad B. Dawood; Adnan A. AbdulRazak; Adel S. Hamadi (Engineering and Technology Journal, 2021)
In this work paraffin oil, water and a mixture of surfactants Span20 & Tween20 are utilized for the preparation of the Metalworking Fluids (MWF). A quadratic model was developed by applying the response surface method (RSM) to relate the droplets size and emulsion stability as a response to five independent variables namely the speed and time of mixing, the concentration of the surfactant, Hydrophilic-Lipophilic Balance (HLB) value and pH value. Analysis of variance (ANOVA) was conducted; the results confirm the high significance of the regression model. The predicted values were found to be satisfactory with that experimental value. Mixing speed exerted the highest effect on the droplet size and the stability of the emulsion. The optimum conditions were found to be (the concentration = 4.75 wt.%, time of mixing = 18.12 min, speed of mixing 14998.93 rpm, pH = 10.01 and HLB = 10.87) to attained Nanoemulsion with 2 nm in size and stability of 24 days. Tool wear and surface roughness were studied at a different speed, the results have shown that the wear ratio of the bits for all selected speeds is as follow: using commercial fluid > MWFs. The metallurgical microscope images have shown that, in case using MWFs the surface of cracks between the metals and the tool is more smooth compare with other fluids.